Answer:
x = 1
Step-by-step explanation:
Given that y varies inversely as x then the equation relating them is
y =
← k is the constant of variation
To find k use the condition y = 5 when x = 3
k = yx = 5 × 3 = 15, thus
y =
← equation of variation
When y = 15 then
15 =
( multiply both sides by x )
15x = 15 ( divide both sides by 15 )
x = 1
x is the 1st number, y is the 2nd number, z is the 3d number.
x+y+z = 2
x - y + z= -2
x - z = y +22 -----> x-y-z=22
x+y+z = 2
<u>x - y + z= -2</u>
2x + 2z =0
x + z = 0
x = -z
x - y + z= -2 and x = -z
-z - y + z = -2, y =2
x-y-z=22 and x = -z, and y = 2 -----> x -2 +x = 22 --->2x = 24 ----> x = 12
x= -z -----> z = - 12
Answer:
B
Step-by-step explanation:
Answer: √0.16
Step-by-step explanation:
√0.16 = 0.4
All of the above. it is a three dimensional pyramid, and a "polyhedron" means it is triangular.